Method and system for enhancing interface performance of optical fiber composite insulator
By forming a nano-TiO2 coating and a modified lightweight composite material matrix on the surface of the fiber fiber, the problem of interface aging of the optical fiber composite insulator core is solved, and the interface performance and reliability are improved.
Patent Information
- Application Number
- CN202411778946.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
During long-term operation, fiber composite insulators have aging of the core interface, resulting in insufficient pores and viscosity, resulting in excessive local electric field strength, increasing the possibility of local discharge and interface breakdown.
The nano-TiO2 coating is formed on the surface of the fiber fiber by the sol-gel method to enhance the surface roughness and surface activity of the fiber fiber, and a silane coupling agent is added to the light composite core matrix material to modify the light composite material matrix to form an optical fiber composite insulating core.
It enhances the bonding ability between interfaces, improves the interface performance of composite materials, and improves the reliability of optical fiber composite insulators.
Smart Images

Figure CN119601319A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of production related to power transmission and transformation insulation equipment, and in particular to a method and system for enhancing the interface performance of an optical fiber composite insulator. Background Art
[0002] There are multiple interfaces in fiber-optic composite insulators. When fiber-optic composite insulators are in long-term operation, the core interface is inevitably affected by aging, forming defects such as pores and insufficient viscosity, which leads to excessive local electric field strength, thereby increasing the possibility of local discharge and interface breakdown. Enhanced processing of fiber interface performance can ensure good adhesion between interfaces of different insulating materials, which can effectively improve the reliability of fiber-optic composite insulator applications. However, domestic research institutions lack research on the treatment of fiber-optic composite insulator interface problems. Therefore, conducting research on fiber / core rod interface treatment technology for fiber-optic composite insulators and analyzing its key parameters of interface performance are of great significance to breaking through the current technical bottleneck of such research in China.
[0003] Nano-TiO2 has excellent properties such as non-toxicity, good chemical stability, good photostability, good corrosion resistance, good electrical properties, good compatibility, high photocatalytic activity, high refractive index and ability to absorb ultraviolet light. It also has high surface area and high surface energy. It can solve the problem of poor bonding between optical fiber and resin and improve the shear strength of composite materials. Summary of the invention
[0004] In order to solve the above problems, the purpose of the present invention is to provide a technology for modifying and enhancing the interface inside the core of a through-type optical fiber composite insulation. Based on the high dispersibility and high surface activity of TiO2, a layer of TiO2 nanofilm is prepared on the surface of the optical fiber by a sol-gel method, aiming to improve the reliability of the optical fiber composite insulator.
[0005] In order to achieve the above technical objectives, the present application provides a method for enhancing the interface performance of an optical fiber composite insulator, comprising the following steps:
[0006] Through the sol-gel method, a nano-TiO2 coating is formed on the surface of the optical fiber to enhance the surface roughness and surface activity of the optical fiber;
[0007] The lightweight composite core matrix material is formed by sequentially adding e51 epoxy resin, methyl hexahydrophthalic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, polyethyl methacrylate polymer hollow microspheres and silane coupling agent, stirring under vacuum and then heating.
[0008] Based on the optical fiber with nano-TiO2 coating, the optical fiber composite insulation core is formed by filling the lightweight composite core matrix material and performing a heating treatment.
[0009] Preferably, in the process of forming the nano-TiO2 coating, the optical fiber is ultrasonically cleaned in ethanol and dried to pre-treat the optical fiber.
[0010] Preferably, in the process of forming the nano-TiO2 coating, the pretreated optical fiber is immersed in a TiO2 dispersion, taken out and dried, and then placed in a room temperature environment to form the nano-TiO2 coating, wherein the TiO2 dispersion is formed by adding anhydrous ethanol to the nano-TiO2 and performing ultrasonic dispersion.
[0011] Preferably, in the process of forming the TiO2 dispersion, 0.5% (0-2%wt) of nano-TiO2 is added to anhydrous ethanol and ultrasonically dispersed for 10 minutes to obtain the TiO2 dispersion.
[0012] Preferably, in the process of forming the nano-TiO2 coating, the pretreated optical fiber is placed in the TiO2 dispersion for 1.0 h, taken out and dried at 60° C. for 15 min, and then placed at room temperature for more than 4 h to form the nano-TiO2 coating.
[0013] Preferably, in the process of using polyethyl methacrylate polymer hollow microspheres, the polyethyl methacrylate polymer hollow microspheres are obtained by adjusting the molar ratio of epoxy resin to methyl hexahydrophthalic anhydride to 1:1, 2,4,6-tris(dimethylaminomethyl)phenol to 0-1.0%wt, and polyethyl methacrylate polymer hollow microspheres to 0-2%wt.
[0014] Preferably, in the process of obtaining the optical fiber composite insulating core, the optical fiber coated with TiO2 film is fixed to the mold and extended from both ends, filled with lightweight composite core matrix material, and then heated at 100°C for 2 hours to obtain the optical fiber composite insulating core.
[0015] Preferably, in the process of using the silane coupling agent, the silane coupling agent includes one of KH550, KH570 or KH591.
[0016] The present invention discloses an interface performance enhancement system for optical fiber composite insulators, which is used to implement the above-mentioned interface performance enhancement method. The system comprises:
[0017] The coating module is used to form a nano-TiO2 coating on the surface of the optical fiber through a sol-gel method to enhance the surface roughness and surface activity of the optical fiber;
[0018] The matrix material preparation module is used to form a lightweight composite core matrix material by sequentially adding e51 epoxy resin, methyl hexahydrophthalic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, polyethyl methacrylate polymer hollow microspheres and silane coupling agent, stirring under vacuum and then heating;
[0019] The optical fiber composite material preparation module is used to form an optical fiber composite insulation core based on an optical fiber with a nano-TiO2 coating by filling a lightweight composite core matrix material and performing a heating treatment.
[0020] Preferably, the system further comprises a control module for executing a method for enhancing the interface performance of an optical fiber composite insulator according to any one of claims 1 to 8, and for controlling the working processes of other functional modules of the system.
[0021] The present invention discloses the following technical effects:
[0022] The present invention enhances the bonding ability between interfaces, improves the interface performance of the composite material, and improves the reliability of the optical fiber composite insulator. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION
[0025] To make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The components of the embodiments of the present application generally described and shown in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the application claimed for protection, but merely represents the selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application.
[0026] like Figure 1 As shown, the present invention provides a method for enhancing the interface performance of an optical fiber composite insulator, comprising the following steps:
[0027] Through the sol-gel method, a nano-TiO2 coating is formed on the surface of the optical fiber to enhance the surface roughness and surface activity of the optical fiber;
[0028] The lightweight composite core matrix material is formed by sequentially adding e51 epoxy resin, methyl hexahydrophthalic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, polyethyl methacrylate polymer hollow microspheres and silane coupling agent, stirring under vacuum and then heating.
[0029] Based on the optical fiber with nano-TiO2 coating, the optical fiber composite insulation core is formed by filling the lightweight composite core matrix material and performing a heating treatment.
[0030] Further preferably, in the method for enhancing interface properties provided by the present invention, during the process of forming the nano-TiO2 coating, the optical fiber is ultrasonically cleaned in ethanol and dried to pretreat the optical fiber.
[0031] Further preferably, in the method for enhancing interface properties provided by the present invention, in the process of forming the nano-TiO2 coating, the pretreated optical fiber is immersed in a TiO2 dispersion, taken out and dried, and then placed in a room temperature environment to form the nano-TiO2 coating, wherein the TiO2 dispersion is formed by adding anhydrous ethanol to the nano-TiO2 and performing ultrasonic dispersion.
[0032] Further preferably, in the method for enhancing interface properties provided by the present invention, in the process of forming a TiO2 dispersion, 0.5% (0-2%wt) of nano-TiO2 is added to anhydrous ethanol and ultrasonically dispersed for 10 minutes to obtain a TiO2 dispersion.
[0033] Further preferably, in the method for enhancing interface properties provided by the present invention, during the process of forming the nano-TiO2 coating, the pretreated optical fiber is immersed in a TiO2 dispersion for 1.0 h, taken out and dried at 60° C. for 15 min, and then placed in a room temperature environment for more than 4 h to form the nano-TiO2 coating.
[0034] Further preferably, in the method for enhancing interfacial properties provided by the present invention, in the process of using polyethyl methacrylate polymer hollow microspheres, the molar ratio of epoxy resin to methylhexahydrophthalic anhydride is 1:1, 2,4,6-tris(dimethylaminomethyl)phenol is 0-1.0%wt, and the polyethyl methacrylate polymer hollow microspheres are 0-2%wt to obtain polyethyl methacrylate polymer hollow microspheres.
[0035] Further preferably, in the method for enhancing interface properties provided by the present invention, in the process of obtaining the optical fiber composite insulating core, the optical fiber coated with TiO2 film is fixed to a mold and extended from both ends, filled with a lightweight composite core matrix material, and then heated at 100°C for 2 hours to obtain the optical fiber composite insulating core.
[0036] Further preferably, in the method for enhancing interface properties provided by the present invention, during the process of using a silane coupling agent, the silane coupling agent includes one of KH550, KH570 or KH591.
[0037] The present invention discloses an interface performance enhancement system for optical fiber composite insulators, which is used to implement the above-mentioned interface performance enhancement method. The system comprises:
[0038] The coating module is used to form a nano-TiO2 coating on the surface of the optical fiber through a sol-gel method to enhance the surface roughness and surface activity of the optical fiber;
[0039] The matrix material preparation module is used to form a lightweight composite core matrix material by sequentially adding e51 epoxy resin, methyl hexahydrophthalic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, polyethyl methacrylate polymer hollow microspheres and silane coupling agent, stirring under vacuum and then heating;
[0040] The optical fiber composite material preparation module is used to form an optical fiber composite insulation core based on an optical fiber with a nano-TiO2 coating by filling a lightweight composite core matrix material and performing a heating treatment.
[0041] Further preferably, the system also includes a control module for executing a method for enhancing the interface performance of an optical fiber composite insulator according to any one of claims 1 to 8, and for controlling the working processes of other functional modules of the system.
[0042] In the interface performance enhancement technology disclosed in the present invention, a nano-TiO2 coating is prepared on the surface of the optical fiber to enhance the surface roughness and surface activity of the optical fiber;
[0043] Nano-TiO2 has a large specific surface area, and the Ti-O bond in TiO2 is highly polar. The water adsorbed on the surface is easily dissociated due to polarization, making it easy to form abundant hydroxyl groups on the surface. This polar group can effectively improve the surface activity of the TiO2 coating and enhance the adhesion performance of the TiO2 coating.
[0044] The lightweight composite material matrix used for the optical fiber composite insulation core is modified by a silane coupling agent to improve the interface bonding ability of the epoxy resin matrix;
[0045] The mechanism of the reaction between silane coupling agent and hydroxyl is to react with the Si-O bond in the silane molecule to form a Si-OC bond. The other end of the molecule contains a functional group that can react with the organic resin, such as an amino group, an epoxy group or a methacryloyl group. The silane coupling agent builds a molecular bridge between the inorganic material and the organic resin, enhancing the interfacial bonding between the two, thereby improving the performance of the composite material.
[0046] The obtained optical fiber is placed in the inner core of a lightweight composite material and cured together to obtain an interface-modified and enhanced optical fiber composite insulation core, wherein the TiO2 coating on the surface of the optical fiber is prepared by a sol-gel method; the silane coupling agent is directly added by adding the coupling agent stock solution when the lightweight material is premixed.
[0047] Embodiment 1: The present invention provides a technology for improving the interface of a composite insulating core of a through-type optical fiber, which specifically includes the following technical contents:
[0048] Step 1: Pretreatment of optical fiber
[0049] The optical fiber was ultrasonically cleaned in ethanol for 2 h to remove surface contaminants and vacuum dried at 60 °C for 10 min to remove residual ethanol.
[0050] Step 2: Preparation of TiO2 dispersion
[0051] Take 0.5% (0-2%wt) of nano-TiO2 and add it to anhydrous ethanol, and disperse it ultrasonically for 10 minutes to obtain the desired TiO2 dispersion.
[0052] Step 3: TiO2 coating preparation
[0053] The cleaned optical fiber was immersed in the TiO2 dispersion for 1.0 h, taken out and dried at 60°C for 15 min, and then placed at room temperature for more than 4 h.
[0054] Step 4: Preparation of lightweight composite core matrix material
[0055] E51 epoxy resin, methyl hexahydrophthalic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, polyethyl methacrylate polymer hollow microspheres (the molar ratio of epoxy resin to methyl hexahydrophthalic anhydride is 1:1, 2,4,6-tris(dimethylaminomethyl)phenol is 0-1.0%wt, polyethyl methacrylate polymer hollow microspheres are 0-2%wt), and KH550 silane coupling agent (KH560 / KH570 / KH591) (0-2%wt) are added in sequence, placed in a vacuum stirrer and stirred under vacuum for 5 minutes, and after being fully mixed, placed in a vacuum drying oven and heated at 80°C for 1 hour to obtain a pre-cured lightweight composite core matrix material.
[0056] Step 5: Optical fiber implanted into the insulating core
[0057] The optical fiber coated with TiO2 film is fixed to the mold and extended from both ends to be filled with the prepared pre-cured lightweight composite material, and then heated at 100°C for 2 hours to obtain the optical fiber composite insulation core after the optical fiber is implanted.
[0058] Step 6: Interface performance test
[0059] The interface enhancement performance is characterized by the interface shear strength. The single-filament tensile test sample is prepared, and the modified lightweight composite material is applied to a single optical fiber and solidified to form microspheres. The diameter of the microspheres and the embedding depth are recorded. The optical fiber sample is then fixed by a fixture, and the fixture is slowly moved upward at a speed of 2mm / min until the tooling scrapes off the resin microspheres. The load during scraping is measured to obtain the optical fiber interface bonding strength. The test results are as follows:
[0060]
[0061] Note: TiO2 coating is obtained by using 0.5%wt dispersion, and silane coupling agent is directly added with a dosage of 1%wt.
[0062] The present invention enhances the bonding ability between interfaces, improves the interface performance of the composite material, and improves the reliability of the optical fiber composite insulator.
[0063] The present invention is described with reference to flowcharts and / or block diagrams of methods, devices (systems), and computer program products according to embodiments of the present invention. It should be understood that each process and / or block in the flowchart and / or block diagram, as well as the combination of processes and / or blocks in the flowchart and / or block diagram, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor, or other programmable data processing device to produce a machine, so that the instructions executed by the processor of the computer or other programmable data processing device generate instructions for implementing the processes in the flowchart and / or block diagram. Figure 1 A process or multiple processes and / or boxes Figure 1 A device that provides the functions specified in a block or multiple blocks.
[0064] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0065] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for enhancing the interface performance of an optical fiber composite insulator, characterized in that: The following steps are involved: Through the sol-gel method, a nano-TiO2 coating is formed on the surface of the optical fiber to enhance the surface roughness and surface activity of the optical fiber; The lightweight composite core matrix material is formed by sequentially adding e51 epoxy resin, methyl hexahydrophthalic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, polyethyl methacrylate polymer hollow microspheres and silane coupling agent, stirring under vacuum and then heating. Based on the optical fiber with nano-TiO2 coating, the optical fiber composite insulation core is formed by filling the lightweight composite core matrix material and heating it.
2. The method for enhancing the interface performance of an optical fiber composite insulator according to claim 1, characterized in that: In the process of forming the nano-TiO2 coating, the optical fiber is ultrasonically cleaned in ethanol and dried to pre-treat the optical fiber.
3. The method for enhancing the interface performance of an optical fiber composite insulator according to claim 2, characterized in that: In the process of forming the nano-TiO2 coating, the pretreated optical fiber is immersed in a TiO2 dispersion, taken out and dried, and then placed in a room temperature environment to form the nano-TiO2 coating, wherein the TiO2 dispersion is formed by adding anhydrous ethanol to the nano-TiO2 and performing ultrasonic dispersion.
4. The method for enhancing the interface performance of an optical fiber composite insulator according to claim 3, characterized in that: In the process of forming the TiO2 dispersion, 0.5% (0-2%wt) of nano-TiO2 is added to anhydrous ethanol and ultrasonically dispersed for 10 minutes to obtain the TiO2 dispersion.
5. The method for enhancing the interface performance of an optical fiber composite insulator according to claim 4, characterized in that: In the process of forming the nano-TiO2 coating, the pretreated optical fiber is immersed in the TiO2 dispersion for 1.0 hour, taken out and dried at 60°C for 15 minutes, and then placed at room temperature for more than 4 hours to form the nano-TiO2 coating.
6. The method for enhancing the interface performance of an optical fiber composite insulator according to claim 5, characterized in that: In the process of using polyethyl methacrylate polymer hollow microspheres, the polyethyl methacrylate polymer hollow microspheres are obtained by using a molar ratio of epoxy resin to methyl hexahydrophthalic anhydride of 1:1, 2,4,6-tris(dimethylaminomethyl)phenol of 0-1.0%wt, and polyethyl methacrylate polymer hollow microspheres of 0-2%wt.
7. The method for enhancing the interface performance of an optical fiber composite insulator according to claim 6, characterized in that: In the process of obtaining the optical fiber composite insulating core, the optical fiber coated with TiO2 film is fixed to the mold and extended from both ends, filled with lightweight composite core matrix material, and then heated at 100°C for 2 hours to obtain the optical fiber composite insulating core.
8. The method for enhancing the interface performance of an optical fiber composite insulator according to claim 7, characterized in that: In the process of using the silane coupling agent, the silane coupling agent includes one of KH550, KH570 or KH591.
9. An interface performance enhancement system for optical fiber composite insulators, characterized in that: The system is used to implement the method for enhancing the interface performance of an optical fiber composite insulator as described in claims 1-8, and the system comprises: The coating module is used to form a nano-TiO2 coating on the surface of the optical fiber through a sol-gel method to enhance the surface roughness and surface activity of the optical fiber; The matrix material preparation module is used to form a lightweight composite core matrix material by sequentially adding e51 epoxy resin, methyl hexahydrophthalic anhydride, 2,4,6-tris(dimethylaminomethyl)phenol, polyethyl methacrylate polymer hollow microspheres and silane coupling agent, stirring under vacuum and then heating; The optical fiber composite material preparation module is used to form an optical fiber composite insulation core based on an optical fiber with a nano-TiO2 coating by filling a lightweight composite core matrix material and performing a heating treatment.
10. The interface performance enhancement system of optical fiber composite insulator according to claim 9, characterized in that: The system also includes a control module for executing a method for enhancing the interface performance of an optical fiber composite insulator as described in any one of claims 1 to 8, and for controlling the working processes of other functional modules of the system.